Strategic Adaption to Marketing Failures: A Case Study of PohonCoklat.co - Abel Widi Astuti; Auramila Divana Esfandiari; Sudarmiatin Sudarmiatin; Ita Prihatining Wilujeng (International Journal Business, Management and Innovation Review, 2025)
This case study examines the business discontinuity of PohonCoklat.co and reconsiders the widely accepted notion that a strong digital marketing strategy alone is sufficient to secure long-term business sutainability. Although the brand achieved notable digital performance–reflected in a steady 4.5% engagement rate accross social media and sustained visibility on major online marketplaces–the business ultimately ceased operations in mid-2023. Using a retrospective qualitative approach that incorporates document analysis and semi-structured interviews, this study reveals that the discontinuity was rooted not in marketing shortcomings, but in critical operational weaknesses. The main contributing factors included owner burnout driven by overly centralized decision-making, intensifying operational burdens caused by rising raw material prices and platform commission fees, and the lack of a scalable, decentralized system to distribute tasks effectively. These structural limitations progressively undermined profitability and constrained the company’s ability to respond to shifts in market demand. The findings highlight that digital marketing success cannot offset core operational deficiencies. Thus, this study asserts that sustainable digital business performance requires a strategic blend of marketing strength, robust operational frameworks, adaptive resource management, and long-term planning. The experience of PohonCoklat.co demonstrates that without these essential components, even digitally strong ventures remain vulnerable to stagnation and eventual closure.